2021
DOI: 10.1038/s41598-021-91921-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrating spatial analysis and questionnaire survey to better understand human-onager conflict in Southern Iran

Abstract: Southern Iran is a conservation priority area for the endangered Persian onager (Equus hemionus onager), which is threatened by habitat fragmentation and conflict with local communities. To better understand factors that influence onager conservation, we administered a questionnaire in local communities to survey their ecological knowledge, personal experience related to onager, and attitudes toward traditional solutions for reducing crop damage by onager. In addition, we used resistant kernel and factorial le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…The vulnerability of these locations is related to the high potential for grey wolf and golden jackal vehicle collisions. Our findings are similar to Moqanaki and Cushman (2017) [ 29 ] and Mohammadi et al (2021) [ 90 ] who showed that core areas for Asiatic cheetah and Persian onager and the corridors that link them are bisected by multiple primary and secondary roads.…”
Section: Discussionsupporting
confidence: 91%
“…The vulnerability of these locations is related to the high potential for grey wolf and golden jackal vehicle collisions. Our findings are similar to Moqanaki and Cushman (2017) [ 29 ] and Mohammadi et al (2021) [ 90 ] who showed that core areas for Asiatic cheetah and Persian onager and the corridors that link them are bisected by multiple primary and secondary roads.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the expansion of onagers' home ranges and their movement from QNP to BPA in the wet season brings them into close proximity with livestock, which may affect onager activity and resource selection (Esmaeili 2020). Over the past decade, a combination of increased enforcement and resource supplementation (water and food additions) have led to a 2.61% increase in the onager population within QNP, leading to increased human-onager conflict in and around BPA (Esmaeili et al 2019;Mohammadi et al 2021). Such conflicts are exacerbated by water shortages and high grazing pressure in BPA, highlighting the need for translocations from QNP as part of broader efforts to reintroduce onagers to large swaths of their historical range.…”
Section: Study Areamentioning
confidence: 99%
“…These human-induced disturbances and mortalities have resulted in widespread species extinctions that are well documented but rarely feature under the HWC discourse (Göttert and Starik 2022). https://www.ecologyandsociety.org/vol28/iss3/art18/ A review of literature shows that studies that model spatially explicit distribution of HWC occurrences are currently few, but on an increasing trajectory (Mohammadi et al 2021, Egri et al 2022, Khosravi et al 2023. This could probably be due to lack of HWC data, which are often sensitive and illegal in nature, thus difficult to access freely (Mateo-Tomás et al 2012, Egri et al 2022.…”
Section: Introductionmentioning
confidence: 99%